work abandonment problems in public construction projects by price search method before and after the support: a case study of the cabinet resolution passed on 17 june 2008. - แก้วตา, ภานุมาศ; ทองอินทร์ดำ, พุทธพล; โตชัยวัฒน์, กองกูณฑ์ (Frontiers in Engineering Innovation Research, 2009)
This research aims at analyzing the problems of work abandonment by contractors with the price search method before and after the Cabinet Resolution concerning measures assisting contractors in public projects, passed on 17 June 2008. The methodology comprises: 1) reviewing the Cabinet Resolution concerning measures assisting contractors in public projects, passed on 17 June 2008, 2 ) reviewing the government procurement regulations and amended B.E.2535 (1992) concerning the price search method, 3 ) finding a number of works abandonment by contractors with the price search method by analyzing the letters of government procurement committee between 17 June 2007 to 17 June 2008 period and 17 June 2008 to 17 June 2009 period, 4 ) analyzing the results by statistics, and 5 ) recommending the results. It was found that the number of work abandonment by price search procurement before the measures are 48 cases and those of after the measures are 32 cases, respectively. The results revealed the measures can reduce the number of work abandonment. However, they should be modified to be in accordance of the economic situation in order to enhance least work abandonment.